Micro-Raman Spectroscopy of Zircon (ZrSiO4) Mineral at Annealing Conditions Usually Applied in Zircon Fission-Track Annealing Dataset - Coelho Dias, Airton Natanael; Leopoldo Constantino, Carlos Jose [UNESP]; Soares, Cleber Jose; Oliveira, Sandro Guedes de (Amer Scientific Publishers, 2020)
Raman analyzes were performed on zircon from a syenite located in the Pocos de Caldas Complex, Brazil, with a fission-track (FT) zircon age of 81.4 +/- 6.8 Ma. Three isochronous heating (1, 10 and 100 hours) of zircon grains were subjected to temperatures between 300 and 750 degrees C. These temperature and times are usually applied to obtain zircon Fission-Track annealing dataset. For each time-temperature conditions, Raman spectra analyses were accomplished. The results show variations in the intensity and FWHM (full width at half maximum) in the main band (1007 cm(-1)-Si-O stretching mode), and a singular change in the peaks from 356 to 439 cm(-1) (Si-O bending mode); and from 202 to 224 cm(-1) (external modes). These changes were interpreted as spectral polarization-dependence related to common crystallinity increases due to the annealing radiation damages and that the thermal treatments do not interfere on the stability of zircon lattice.
Keywords: Zircon; Raman Spectroscopy; Annealing Dataset; Thermal Treatment; Pocos de Caldas Complex